Floor of the Mouth Hemorrhage Following Dental Implant Placement or Guided Bone Regeneration (GBR) in the Atrophic Interforaminal Mandible - Domenico Sfondrini; Stefano Marelli; Rachele Patriarca; Andrea Scribante; Lorenzo Preda; Gabriele Savioli; Giorgio Novelli; Alessandro Bardazzi (Case Reports in Dentistry)
The authors present two cases of mouth floor hemorrhage consequences of implant placement within the atrophic anterior mandible. In one patient, the implant placement was associated with the guided bone regeneration (GBR) technique. This serious complication has been widely described in the literature, especially in the anterior mandible area. In cases of bone resorption, the edentulous ridge becomes closer to the artery, and the risk of vessel injury increases. In both patients, the hematoma rapidly spread in the loose tissues of the mouth floor, displacing the tongue posteriorly and cranially, with airway compromise. The patients were hospitalized with nasotracheal intubation to secure the airway. In both patients, the bleeding stopped spontaneously, and after a few days, the oral floor swallowing was reduced, allowing the endotracheal tube to be removed. In about 2 weeks, the hematoma completely resorbed without surgery. According to the literature, the main cause of floor of the mouth hemorrhage is the mandibular lingual cortical plate perforation during bone drilling with subsequent sublingual–submental artery injury. In fact, in the first patient presented, this surgical error was clearly noticeable on the CT scan. Differently, in the second case reported, no radiological signs of inner cortical perforation were observed, and together with a mouth floor hematoma, a blood collection was also evident on the lower lip, suggesting a different cause of bleeding. Most likely during the periosteal release incision, mandatory in GBR technique, the ascending mental artery was injured, and hematoma spread in the mouth floor through the similar incision done on the lingual flap. Firstly, the mouth floor hemorrhage caused by an injury of a vestibular soft tissue artery during GBR surgery was reported. Strategies and recommendations to avoid this life-threatening event are provided, based on the literature review and the authors’ experience.